"I love China, but…”: The imbalanced interplay of demand, control, and support in the adaptation of Ethiopian students in China - Yang, Demei; Zeng, Xiangmin (Journal of International Students, 2026)
International academia has shown a growing interest in African student migration to China. However, comprehensive investigations grounded in the specific cultural contexts of these students, rather than treating “Africa” as a monolith, remain notably scarce. To advance research on African student migration, this study examines the adaptation of Ethiopian students dispatched by the government in China. Grounded in the demand-control-support (DCS) model, this qualitative study employs an ethnographic case study design. The findings reveal an unbalanced adaptation process characterized by high demands (language, religion, academics), structurally low control, and a consequent reliance on support as the primary buffering mechanism. The study concludes that achieving balanced adaptation requires enhancing student control through the development of global competence and strengthening proactive institutional support, offering a novel application of the DCS model to student mobility.